Comparison between selective and routine intensive care unit admission post-supraglottoplasty. (August 2017) - Cooper, Timothy; Harris, Bree; Mourad, Ahmed; Garros, Daniel; El-Hakim, Hamdy
Abstract: Objective: To compare major post-operative respiratory complications, post-operative disposition and duration of hospital admission before and after adopting a selective intensive care unit (ICU) admission care plan following supraglottoplasty (SGP). Methods: Retrospective case series set in a tertiary pediatric referral center. Eligible patients undergoing SGP between October 2003 and July 2015 were identified through a prospectively kept surgical database. Historical cohorts with routine admission to ICU and selective admission to ICU were identified based on a shift in surgeon practice. The cohorts were compared with respect to demographics, presenting features, endoscopic findings, baseline sleep and swallowing study results, major respiratory complications (including repeat or unplanned ICU admission or intubation) and length of post-operative hospital admission. Results: 141 eligible patients were identified with 35 children in the routine ICU admission cohort and 106 in the selective ICU admission cohort. There were no significant differences between cohorts regarding major respiratory complications with only one patient in the selective ICU admission cohort requiring an unplanned admission to ICU (P = 1.00, Fisher's exact test). This gives a number needed to harm of 78 step-down unit admissions for 1 unplanned ICU admission. The rate of ICU admission was reduced from 71% to 26% with adoption of a selective ICU admission care plan (p < 0.01, χ 2 ). Mean duration of post-operative hospitalization was reduced from 5.1 ± 3.5 days to 1.9 ± 2.3 days (P < 0.01, Student's t-test). Conclusions: Selective post-operative ICU admission following SGP significantly reduces ICU utilization and may reduce length of hospital stay without compromising safety and care. This has significant cost benefit implications.